Determinants of the Agricultural Exports in Azerbaijan - Ibrahim Niftiyev (SSRN, 2020)
Oil booming and accumulated mineral revenue contributed to the economic growth in Azerbaijan since independence but also pressurized the national currency leading to the appreciation of the nominal effective exchange rate (NEER) and real effective exchange rate (REER). An increase in export prices makes them expensive, decreasing the competitiveness of the country. Azerbaijan's recent decreased economic performance during 2014–2015 reflected a common reality among the resource exporting countries: relying on the primary sectors might jeopardize the national economy due to the extreme price volatility. The paper investigates the extension of the relationship between NEER, REER, and other export-related macroeconomic variables and agricultural exports to identify Azerbaijan's non-oil sub-sectoral dynamics between 2001–2018 via the OLS estimations. The main findings indicate that NEER negatively impacted potato, fresh fruit, and fresh vegetable exports. Moreover, potato and fresh fruit exports demonstrated more stable export dynamics during the economic crisis periods.
Keywords: 330; Azerbaijan economy; nominal effective exchange rate; real effective exchange rate; agriculture; crop exports